The effect of exercise during pregnancy on gestational diabetes mellitus in normal-weight women: a systematic review and meta-analysis - Ming, Wai-Kit; Ding, Wenjing; Zhang, Casper J. P.; Zhong, Lieqiang; Long, Yuhang; Li, Zhuyu; Sun, Cong; Wu, Yanxin; Chen, Hanqing; Chen, Haitian; Wang, Zilian (BMC pregnancy and childbirth, 2018)
Gestational diabetes mellitus (GDM) is one of the most common complications during pregnancy, and it has both short- and long-term adverse effects on the health of mothers and fetuses. To investigate the effect of exercise during pregnancy on the occurrence of GDM among normal-weight pregnant women. We searched for studies published between January 1994 and June 2017 that appeared in the Web of Science, Scopus, ClinicalTrials.gov or Cochrane library databases. Randomized controlled trials that investigated the preventive effect of exercise on GDM in normal-weight women were included. Interventions including any confounding factors (e.g., dietary) were excluded. We extracted maternal characteristics, the diagnostic criteria of GDM, and basic information for intervention and obstetric outcomes. The primary outcome was the occurrence of GDM, and the secondary outcomes included gestational weight gain, gestational age at birth, birth weight, and the odds of cesarean section. A meta-analysis was conducted based on calculations of pooled estimates using the random-effects model. Eight studies were included in this systematic review and meta-analysis. Exercise during pregnancy was shown to decrease the occurrence of GDM [RR = 0.58, 95% CI (0.37, 0.90), P = 0.01 and RR = 0.60, 95% CI (0.36, 0.98), P = 0.04 based on different diagnosis criteria, respectively] in normal-weight women. Regarding secondary outcomes, exercise during pregnancy can decrease gestational weight gain [MD = - 1.61, 95% CI (- 1.99, - 1.22), P<0.01], and  had no significant effects on gestational age at birth [MD = - 0.55, 95% CI (- 1.57, 0.47), P = 0.29], birth weight [MD = - 18.70, 95% CI (- 52.49, 15.08), P = 0.28], and the odds of caesarean section [RR = 0.88, 95% CI (0.72, 1.08), P = 0.21], respectively. Exercise during pregnancy can ostensibly decrease the occurrence of GDM without reducing gestational age at delivery and increasing the odds of cesarean section in normal-weight women.